EVOLUTION OF STRATEGIES FOR HUMAN CAPITAL DIAGNOSTICS - Deriugin, Pavel; Glukhikh, Vladimir; Yarmak, Olga; Strashko, Ekaterina; Kamyshina, Elena; Yarmak, Veronika (Revista Inclusiones, 2021)
The strategies for human capital diagnostics depend on the ideas about the nature of human capital, which change with the social and economic development of society. Over the past three centuries, the concepts of human capital have evolved, leading to the evolution of ideas and diagnostic strategies. However, there is an obvious contradiction in modern strategies for human capital diagnostics. It consists in focusing on the study of factors external to the personality that affect human capital, which was characteristic of the industrial society. Along with this, modern theoretical studies of the nature of human capital reveal the important role of personality values in the structure of human capital, values that link knowledge, skills and abilities of an individual with motivation and interests, without which “purely” professional competencies may be ineffective. On the basis of the analysis of the history and modern understanding of human capital, the authors of the article make a conclusion that it is advisable to develop a sociological diagnosis of the human capital of a person focused on the study of values.